Acute infusion reactions induced by monoclonal antibody therapy. (January 2011) - Maggi, Enrico; Vultaggio, Alessandra; Matucci, Andrea
This article reports recent evidence on epidemiological data concerning monoclonal antibody (mAb) infusion-related anaphylaxis, as well as recent data on the correlation between mAb immunogenicity and safety profiles. Pathogenic mechanisms of mAb-related adverse reactions including hypersensitivity, IgE- and non-IgE-mediated events and cytokine release syndrome are also highlighted. Finally, the role of serum anti-mAb antibodies as markers to monitor the safety of such therapeutical compounds are extensively evaluated. The anaphylaxis occurring during therapy with the anti-TNF-α mAb infliximab, largely used in immune-mediated diseases, has been taken as a paradigm